2017
DOI: 10.24912/ja.v19i1.117
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Akuntansi Murabahah Terhadap Pembiayaan Kredit Pemilikan Rumah Pada Bank Syariah Mandiri Cabang Luwuk

Abstract: Penelitian ini termasuk jenis penelitian terapan. Teknik pengumpulan data yang digunakan adalah teknik dokumentasi dan kepustakaan. Data yang digunakan adalah data primer dan data sekunder serta metode analisis data yang digunakan adalah metode deskriptif kualitatif. Hasil analisis menunjukan bahwa pembiayaan Kredit Kepemilikan Rumah (KPR) pada Bank Syariah Mandiri Cabang Luwuk telah sesuai dengan Pernyataan Standar Akuntansi Keuangan Nomor 102 tentang Akuntansi Murabahah. Di dalam pelaksanaan pembiayaan murab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The seller in a Murabahah deal covers the difference between the purchase and selling prices. The profit margin is the difference between the selling and cost prices (Nasir & Sululing, 2017). In Islamic law, the term "Murabahah" refers to a specific type of sale in which the vendor discloses the total cost of acquiring the merchandise (including the price of the merchandise itself and any extra expenses incurred in acquiring the merchandise) as well as the anticipated margin (profit).…”
Section: B Theoretical Study 1 Murabahahmentioning
confidence: 99%
“…The seller in a Murabahah deal covers the difference between the purchase and selling prices. The profit margin is the difference between the selling and cost prices (Nasir & Sululing, 2017). In Islamic law, the term "Murabahah" refers to a specific type of sale in which the vendor discloses the total cost of acquiring the merchandise (including the price of the merchandise itself and any extra expenses incurred in acquiring the merchandise) as well as the anticipated margin (profit).…”
Section: B Theoretical Study 1 Murabahahmentioning
confidence: 99%
“…A few number of research also showed the need for changes and additional policies in murābahah contract (Wulandari et al, 2016;Maryanti et al, 2016). Furthermore, some findings indicated the suitability of the implementation between murābahah accounting, PSAK and Islamic law (Luayyi, 2005;Hanum, 2014;Nasir and Sululing, 2015;Hasmitha and Ja'far, 2012;and Kholis, 2007). In addition, Buziek's (2011) stated that there are similarities in the implementation of PSAK Number: 102 in Islamic banking system, except for tax regulations due to the differences associated with the regulations .…”
Section: Introductionmentioning
confidence: 99%